Orexin and MCH neurons: regulators of sleep and metabolism - Bouâouda, Hanan; Jha, Pawan Kumar (Frontiers in Neuroscience, 2023)
Sleep-wake and fasting-feeding are tightly coupled behavioral states that require coordination between several brain regions. The mammalian lateral hypothalamus (LH) is a functionally and anatomically complex brain region harboring heterogeneous cell populations that regulate sleep, feeding, and energy metabolism. Significant attempts were made to understand the cellular and circuit bases of LH actions. Rapid advancements in genetic and electrophysiological manipulation help to understand the role of discrete LH cell populations. The opposing action of LH orexin/hypocretin and melanin-concentrating hormone (MCH) neurons on metabolic sensing and sleep-wake regulation make them the candidate to explore in detail. This review surveys the molecular, genetic, and neuronal components of orexin and MCH signaling in the regulation of sleep and metabolism.